Caffeic Acid Genotoxicity: Correlation of the Pig‐a Assay with Regulatory Genetic Toxicology In Vivo Endpoints. (30th September 2019) - Bhalli, Javed A.; Neft, Robin; Noteboom, Jessica; Tebbe, Cameron C.; Chan, Michelle; Kuhn, Kylie; Pearce, Gareth; Jordan, Liam; Beevers, Carol
Abstract : Caffeic acid is found in variety of fruits and vegetables. It is considered as possible human carcinogen (Group 2B). It is negative in Ames and mouse micronucleus (MN), but positive in mouse lymphoma and chromosomal aberration assays. The objective of this study was to evaluate the in vivo genotoxicity of caffeic acid using three different endpoints: in vivo MN, Pig‐a, and comet assay. Two sets of six rats per group were administered vehicle (0.5% hydroxypropyl methylcellulose), 500, 1, 000, or 2, 000 mg/kg/day of caffeic acid for three consecutive days via oral gavage. One set of animals was used for the Pig‐a and MN assay and the other set was used for the comet assay. N‐ Ethyl N‐ Nitrosourea was used as positive control for the Pig‐a and MN assay, and ethyl methanesulfonate for the comet assay. From one set of animals, peripheral blood was collected on Days −1, 14, and 30 for the Pig‐a assay and on Day 4 for the MN assay. The other set of animals was euthanized 3 hr after the last dose; liver and blood were collected for the comet assay. A statistically significant increase in the MN frequency was observed at 2, 000 mg/kg/day. No increase in the red blood cells (RBC CD59‐ ) or reticulocytes (RET CD59‐ ) Pig‐a mutant frequencies was observed on Days 14 or 30. No increase in DNA strand breaks was observed in the peripheral blood or liver in the comet assay. Environ. Mol. Mutagen. 2019. © 2019 Wiley Periodicals, Inc.